THE CRIME OF FORCED MARRIAGE AGAINST CHILDREN IN THE PERSPECTIVE OF CRIMINAL LAW - Azisa, Nur; Syamsuddin Muchtar; M. Aris Munandar; Ismail Iskandar; Nurul Hikmah; Fhildzha Zhafirin (Awang Long Law Review, 2023)
Child marriage is a phenomenon that stilloccurs frequently in Indonesia today. After the promulgation of The Law of the Republic of Indonesia Number 12 Year2022 concerning Crimes of Sexual Violence(TPKS Law), child marriage is categorizedas a criminal act of sexual violence basedon forced child marriage. The criminalprovisions related to forced child marriages, the TPKS Law is disharmony with The Law of the Republic of Indonesia Number 16 Year 2019 concerning Amendments to The Law of the Republic of Indonesia Number 1 Year 1974 concerning Marriage (MarriageLaw), in which the law accommodates thepossibility of filing a dispensation with ageand cultural considerations. Meanwhile, thisis very inconsistent with the principlesadhered to in the TPKS Law. So that thiscan lead to obscuur libel (obscurity) in lawenforcement in the future. Given that theTPKS Law still does not have to implementregulations, it is still classified as an aspiredlaw (ius constituendum).